2015
DOI: 10.1002/fsn3.289
|View full text |Cite
|
Sign up to set email alerts
|

Application of hydrolyzed proteins of animal origin in processed meat

Abstract: With increasing consumer interest in functional foods, proteins from slaughterhouse side streams can offer interesting application opportunities in this respect. Worldwide, increasing numbers of people are suffering from hypertension and protein deficiency. Hydrolyzed proteins of animal origin may show ACE‐inhibitory activity, which is central to the treatment of hypertension. Furthermore, the protein content of, for example, meat products increases markedly through the addition of hydrolyzed proteins, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The first part of 241 the questionnaire consisted of seven sheets (one for each sample), where consumers were asked 242 to first evaluate the overall acceptability on a 9-point hedonic scale, and then to complete a 243 check-all-that-apply (CATA) questionnaire with the following 20 attributes: Artificial, Bitter, 244 were developed with point of departure on existing sensory literature on processed meat (e.g. 247 Meinert et al, 2015), and later refined and modified based on qualitative tastings among the 248 attributes to the test samples and that they were easily understood by the consumers. 250…”
Section: Participants 217mentioning
confidence: 99%
See 3 more Smart Citations
“…The first part of 241 the questionnaire consisted of seven sheets (one for each sample), where consumers were asked 242 to first evaluate the overall acceptability on a 9-point hedonic scale, and then to complete a 243 check-all-that-apply (CATA) questionnaire with the following 20 attributes: Artificial, Bitter, 244 were developed with point of departure on existing sensory literature on processed meat (e.g. 247 Meinert et al, 2015), and later refined and modified based on qualitative tastings among the 248 attributes to the test samples and that they were easily understood by the consumers. 250…”
Section: Participants 217mentioning
confidence: 99%
“…Finally, it should also be kept in mind that the lack of concept calibration 523 may have cause consumers not to use unfamiliar terms (such as "umami") reliably, and that a 524 MPH as a functional ingredient in food applications. To the best of our knowledge, the only 532 other paper in this area that is a study by Meinert and colleagues (Meinert et al, 2015), focusing 533 on sensory properties of MPH enriched saveloy obtained from different types of hydrolysates, 534 and found that the source of hydrolysates the slaughterhouse side stream had an impact on the 535 sensory profile, but not concentration (up to 8%), affected the sensory quality. Here, we extend 536 these previous results with an even larger range of MPH concentration and a wider range of 537 product variation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Common preparation methods for these hydrolysates include enzymatic hydrolysis, solvent extraction, and microbial fermentation (Vijaykrishnaraj and Prabhasankar 2015;Hou et al 2017). Other common sources for protein hydrolysates includes maize, canola, egg white and yolk albumin, casein, whey, soybean, meat and pork among others (McCarthy et al 2013;Lene Meinert et al 2016).…”
Section: Introductionmentioning
confidence: 99%